2015
DOI: 10.3892/ol.2015.3488
|View full text |Cite
|
Sign up to set email alerts
|

Fibroadenoma with an unexpected lobular carcinoma in situ: A case report and review of the literature

Abstract: Abstract. Fibroadenoma (FA) is the most common type of breast lesion in young female individuals. Although malignant transformation in FA is rare, there is evidence of an association with breast carcinoma, particularly in middle-aged females with associated risk factors, such as a strong family history and/or BRCA-1/2 mutations. The current study presents the case of a 44-year-old female exhibiting lobular carcinoma in situ (LCIS) arising within an FA. Over the previous 20 years, numerous lumps were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Hua et al [27] reported that though the malignant transformation of fibroadenoma is very rare, the incidence of breast carcinoma within fibroadenoma is estimated at 0.1% to 0.3% and fibroadenoma may be a risk factor for malignant breast disease in the middle age. Similarly, the risk of breast carcinoma is 2.17, 3.1 and 3.88 times higher in patients with simple, complex and benign proliferative diseases adjacent to fibroadenoma respectively [30]. In our study, the age of our patient appears to be very low compared to mean age of 46.9 years reported by Wu et al [31] in Taiwan.…”
Section: Characteristics Of Fibroadenoma In Nigerian Igbo Femalessupporting
confidence: 41%
“…Hua et al [27] reported that though the malignant transformation of fibroadenoma is very rare, the incidence of breast carcinoma within fibroadenoma is estimated at 0.1% to 0.3% and fibroadenoma may be a risk factor for malignant breast disease in the middle age. Similarly, the risk of breast carcinoma is 2.17, 3.1 and 3.88 times higher in patients with simple, complex and benign proliferative diseases adjacent to fibroadenoma respectively [30]. In our study, the age of our patient appears to be very low compared to mean age of 46.9 years reported by Wu et al [31] in Taiwan.…”
Section: Characteristics Of Fibroadenoma In Nigerian Igbo Femalessupporting
confidence: 41%
“…FAD is a common type of benign breast lesion with a reported incidence rate of 7-13% in female individuals and commonly in the second and third decades of life [6]. A carcinoma arising in a FAD is extremely rare, with an incidence of 0.02% to 0.125% [1,7,12].…”
Section: Discussionmentioning
confidence: 99%
“…FAD may occur at any age, however is mostly encountered in premenopausal women and the peak age of incidence is the second and third decade of life [6]. On histology FAD is a benign tumour composed of both epithelial and stromal components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LN may also be found adjacent to tubular BC and columnar cell lesions of the mammary epithelium ("Rosen triad") [132]. Pure LN without invasive BC may be encountered as an incidental finding in core needle biopsies (CNBs), reduction mammoplasties and benign lesions, such as fibroadenomas [133][134][135][136]. LN is often multifocal and bilateral [137].…”
Section: Related In Situ Lesionsmentioning
confidence: 99%